Next Steps in Decolonising Aboriginal and Torres Strait Islander Primary Health Care Policy in Australia: An Analysis of Key Stakeholder Views - D’Angelo, Shane; Fisher, Matthew; Mackean, Tamara; O’Donnell, Kim; Dwyer, Judith; Sherwood, Juanita; Ziersch, Anna; Freeman, Toby; Shakespeare, Madison; Askew, Deborah; Browne, Annette; Baum, Fran (The International Indigenous Policy Journal, 2024)
Following a failed 2023 referendum on constitutional recognition of Aboriginal and Torres Strait Islander people, Australian governments must work with Indigenous leaders to chart a new way forward in policy to support Indigenous health and wellbeing. Here we report on key stakeholder views on what is required to decolonise Indigenous primary health care (PHC) policy. This article reports on qualitative research conducting yarns with 20 senior staff working in key government and non-government organisations comprising the Indigenous PHC sector (‘stakeholders’). Stakeholders see the sector as exemplifying decolonisation, motivated through Indigenous leadership. However, further changes are needed in mainstream health services, workforce development, intersectoral policy, and determinants of health. We discuss how the Indigenous PHC sector can inform decolonising policy in other sectors and reflect on the international implications of our findings. We conclude that the sector provides important lessons for decolonising Australian public policy.